Discrimination of Mainlobe Deceptive Target With Meter-Wave FDA-MIMO Radar - Liu, Yibin; Wang, Chunyang; Gong, Jian; Chen, Geng (IEEE communications letters, 2022)
Frequency diverse array multiple-input multiple-output (FDA-MIMO) communication regime has received a lot of attention in the field of point-to-point communication and interference suppression due to its degrees of freedom in the range domain. Previous researches have mainly considered non-coherent source scenarios. However, FDA-MIMO communication system in low-elevation is subject to multipath effects in addition to the potential threats within the mainlobe. The discrimination of true and false targets using meter-wave FDA-MIMO radar in low-elevation scenarios is still a problem that needs to be addressed. This letter mainly derives the signal model of the mainlobe deceptive jamming acting on the meter-wave FDA-MIMO radar and proposes a method for the discrimination of true and false targets. Simulation results verify the effectiveness of the proposed method.